Application of the Duty not to Cause Significant Harm in the context of the Nile River Basin - Mengesha, Zewdu (Bahir Dar University Journal of Law, 2022)
The duty not to cause significant harm is an obligation of customaryinternational law relating to utilization of international watercourses. Thisduty requires a state sharing freshwater resources to refrain from causingsignificant harm to other states through its use of a shared internationalwatercourse. It also requires consideration of all relevant factors that areessential for its effective implementation in any given internationalwatercourse. In relation to this duty, the Nile Basin States adopted the NileBasin Cooperative Framework Agreement to regulate the use, development,protection, conservation and management of the Nile River Basin and itsresources. However, the Nile River Basin Cooperative Framework Agreementdid not set out detailed guidelines on how the Nile River Basin Commissionshould promote and facilitate the implementation of the principles enshrinedunder this Framework convention, which includes the duty not to causesignificant harm. This entails drawbacks for the application of the principlein the Nile Basin. Thus, this Article examines how the duty not to causesignificant harm should be applied in the Nile Basin.